2021
DOI: 10.1371/journal.pone.0248044
|View full text |Cite|
|
Sign up to set email alerts
|

Self-referential encoding of source information in recollection memory

Abstract: Information that is encoded in relation to the self has been shown to be better remembered, yet reports have disagreed on whether the memory benefit from self-referential encoding extends to source memory (the context in which information was learned). In this study, we investigated the self-referential effect on source memory in recollection and familiarity-based memory. Using a Remember/Know paradigm, we compared source memory accuracy under self-referential encoding and semantic encoding. Two types of sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
5
3
0
Order By: Relevance
“…We found an SRE for inherent (question type), but not peripheral (background image), source memory across all ages. This is in line with recent findings by Lawrence and Chai (2021), who showed the same inherent versus peripheral source SRE difference in adults. For the younger age range of our sample, we compare to Cunningham et al's study (2014) of 4-to 6-year-olds in which an SRE was found for the referent (source memory; self or other) when it was intentional (inherent) or incidental to the task.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We found an SRE for inherent (question type), but not peripheral (background image), source memory across all ages. This is in line with recent findings by Lawrence and Chai (2021), who showed the same inherent versus peripheral source SRE difference in adults. For the younger age range of our sample, we compare to Cunningham et al's study (2014) of 4-to 6-year-olds in which an SRE was found for the referent (source memory; self or other) when it was intentional (inherent) or incidental to the task.…”
Section: Discussionsupporting
confidence: 93%
“…This increasing reaction time for self-relative to semantic encoding may suggest that self-referential processing during encoding promotes longer processing and leads to a richer representation of the item as individuals get older. However, as seen in other studies (Ghetti et al, 2010;Lawrence & Chai, 2021), recognition accuracy did not correlate with reaction time. Furthermore, including reaction time as a covariate in the main analyses did not influence the results, and the correlation between SRE score and the difference in reaction time between conditions was not significant, suggesting that the observed SRE was not due to increased exposure time alone.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations